2009
DOI: 10.2215/cjn.02410508
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Autosomal Dominant Polycystic Kidney Disease Patients not yet on Dialysis

Abstract: Conclusions: Predialysis ADPKD patients assess their quality of life similar to the general population. Age, BMI, pulse pressure, pain medication intake, and education level link to their physical well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 24 publications
3
69
0
7
Order By: Relevance
“…TKV associates with the development of ESRD and significantly affects patients' quality of life (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…TKV associates with the development of ESRD and significantly affects patients' quality of life (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Pain has been reported as a very frequent symptom of ADPKD patients, affecting up to 60% of them 15,32 and jeopardizing their quality of life. 33 Because that symptom involves a series of sensorial qualities and subjective aspects, 22,32 it requires a careful investigation by a multiprofessional team. Duarte et al 23 have emphasized the importance of using proper instruments to assess the situations and experiences in the health area, so that reliable information is obtained.…”
Section: Results Translation and Transcultural Adaptation Of The Quesmentioning
confidence: 99%
“…A number of studies have investigated symptom burden in ADPKD patients [5,7,8,9]. The largest of these studies did not find an association between kidney volume and pain, except for a small subgroup with very large kidneys [5].…”
Section: Introductionmentioning
confidence: 99%
“…The largest of these studies did not find an association between kidney volume and pain, except for a small subgroup with very large kidneys [5]. Another study concluded that quality of life was not different between patients with a total kidney volume (TKV) larger or smaller than 1,000 mL, but the effect of liver volume was not assessed [8]. Two studies that analyzed the effect of liver volume on quality of life, showed conflicting results, with one study finding no relation and the other a significant, but weak association between liver volume and symptom burden [10,11].…”
Section: Introductionmentioning
confidence: 99%